Anti-cancer activity of triterpenoids isolated from Luvunga Scandens against MCF-7 cells - Putri Nur Hidayah Al-Zikri binti Mohamad Akil (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2015)
Luvunga scandens belong to the family of Rutaceae which usually inhabits tropical and moist environment. This plant is known as 'Mengkurat Jakun' among locals and used traditionally to treat fever and fatigue via decoction. The study aimed to elucidate the compounds from L. scandens stem, which were isolated using bioactivity guided isolation together with their mechanism of action on human breast cancer cell (MCF-7). The bioactivity-guided isolation of cytotoxic agent of the stem of L. scandens resulted in the isolation and characterization of a new triterpenoid from this species, 3-oxotirucalla-7,24-dien-21-oic-acid (2), along with a known triterpenoid, flindissol (1). The isolation was conducted using chromatographic techniques on silica gel and sephadex LH-20. The structures of the isolated compounds were elucidated on the basis of spectroscopic analysis including UV, IR, NMR, MS and 2D NMR. The cytotoxic activity of the plant on the proliferation of MCF-7 cell line was evaluated by MTT, WST-1 assay, scanning electron microscope (SEM), flow cytometry and RT-qPCR. The cytotoxic evaluation of the extracts showed that IC50 value of the dichloromethane (LSC-SD) and methanol (LSC-SM) extracts from the stem were 75.0 and 77.0 µg/mL respectively. Whereas IC50 value of n-hexane (LSF-H), n-hexane:DCM (LSF-HD), DCM (LSF-D) and DCM:MeOH (LSF-DM) fraction extracts were 97.5, 35, 98.9 and 94 µg/mL respectively. The IC50 value of MeOH (LSF-M) fraction could not be extrapolated since none of the concentration of this extract was able to reduce the proliferation activity to 50 %. Compound 1 and 2 showed potent cytotoxicity against MCF-7 cell line with IC50 values of 13.8 µM and 27.5 respectively after 24 h of treatment. Doxorubicin was used as a positive control drug with IC50 values of 6.21 µM. Morphological analysis of the cells surface exhibit the apoptosis results after 24 h treated with LSC-SD extract, 1 and 2, where the cells were rounded up, shrank and lost contact with neighboring cells. Apoptosis of MCF-7 cells treated with both compounds were confirmed by flow cytometry. The results show that compound 1 and 2 exert their anti-proliferative effect on MCF-7 cells through inhibiting cell cycle where the distribution of cells at Sub G1 phase was 7.7 and 9.3 % respectively. Further evident of apoptosis induction by compound 1 and 2 towards MCF-7 cell lines were assayed by RT-qPCR on the expression of PUMA, caspase-8 and caspase-9. In this assay, both compounds showed the increased of the expression of PUMA, caspase-8 and caspase-9 gene. In conclusion, both triterpenoids, 3-oxotirucalla-7,24-dien-21-oic-acid (2) and flindissol (1) have a potential to be developed as anticancer agents against breast cancer.